Existence of Multiple Solutions for a Singular Elliptic Problem with Critical Sobolev Exponent - Zonghu Xiu (Abstract and Applied Analysis)
We consider the existence of multiple solutions of the singular elliptic problem , as , where , , , , , , . By the variational method and the theory of genus, we prove that the above-mentioned problem has infinitely many solutions when some conditions are satisfied.